Unlocking the therapeutic mechanism of Caesalpinia sappan: a comprehensive review of its antioxidant and anti-cancer properties, ethnopharmacology, and phytochemistry - Asevedo, Estéfani Alves; Ramos Santiago, Livia; Kim, Hyo Jeong; Syahputra, Rony Abdi; Park, Moon Nyeo; Ribeiro, Rosy Iara Maciel Azambuja; Kim, Bonglee (Frontiers in Pharmacology, 2025)
Herbal medicine are an invaluable reservoir of bioactive compounds, offering immense potential for novel drug development to address a wide range of diseases. Among these, Caesalpinia sappan has gained recognition for its historical medicinal applications and substantial therapeutic potential. This review explores the ethnopharmacological significance, phytochemical composition, and pharmacological properties of C. sappan, with a particular focus on its anticancer activities. Traditionally, C. sappan has been utilized for treating respiratory, gastrointestinal, and inflammatory conditions, demonstrating its broad therapeutic scope. The plant’s rich array of bioactive compounds—flavonoids, triterpenoids, phenolic acids, and glycosides—forms the basis of its potent antioxidant, anti-inflammatory, and pharmacological effects. Modern pharmacological research has further substantiated its versatility, revealing anticancer, anti-diabetic, anti-infective, and hepatoprotective properties. However, significant challenges remain, including the need to unravel the precise molecular mechanisms underlying its anticancer effects, refine extraction and isolation methods for bioactive compounds, and validate its safety and efficacy through well-designed clinical trials. Particularly noteworthy is C. sappan’s potential in combination therapies, where it may synergistically target multiple cancer pathways, enhance therapeutic outcomes, and mitigate adverse effects. This review synthesizes the findings from the past decade, providing a comprehensive evaluation of C. sappan’s pharmacological promise while identifying critical areas for future research. By addressing these gaps, C. sappan could serve as a cornerstone for innovative therapeutic strategies, offering hope for improved management of cancer and other complex diseases.